Comparison of the immunogenicity of ChAdOx1 nCoV-19 vaccine against the wild-type and delta variants in kidney transplant recipients and healthy volunteers - Watcharananan S.P. (2023)
Little is known about immunogenicity after ChAdOx1 nCov-19 vaccination after transplantation. We assessed the vaccine response by antibody testing, surrogate neutralization test (sVNT) against wild-type (WT) and delta variant (DT), and T cell assay in 83 kidney transplant recipients (KTRs) and 52 healthy volunteers (HVs). For KTRs, a positive anti-RBD antibody was seen in 2.8% after one dose and 15.7% after two doses of the vaccine. After two doses, the positivity rate by sVNT was equal (4.9% each, for WT and DT) and was 13.4% by T cell response. Post two doses, KTRs had significantly lower geometric mean titer than HVs (1.93 [95% CI: 1.39–2.69] vs. 248.3 [95% CI: 203.7–302.6] BAU/ml, respectively, p <.001). Daily mycophenolate dose of ≥1000 mg significantly associated with negative seroconversion [risk ratio (RR) of 0.33, 95% CI: 0.15–0.72, p =.005]. Compared with cyclosporine, daily tacrolimus dose of ≤3 mg and >3 mg of tacrolimus significantly associated with negative seroconversion [RR = 0.38 (95% CI, 0.17–0.85, p =.018) and RR = 0.16 (95% CI, 0.37–0.73, p =.018)], respectively. The vaccine was safe and well-tolerated but the immune response after the two doses of ChAdOx1 nCov-19 vaccine in KTRs was very low.